Superconducting radio frequency photoinjectors for CW-XFEL - Xiang, R.; Arnold, A.; Lewellen, J. W. (Frontiers in Physics, 2023)
A dependable and consistent electron source is a crucial requirement for the achievement of high-power free electron lasers (FELs). Over the past two decades, it has been demonstrated that photoinjectors based on SRF technology (SRF guns) are suitable for continuous wave (CW) beam generation. SRF guns possess both the high accelerating field gradients of normal conducting RF photoinjectors and the low power dissipation thanks to mature SRF cavity technology, and therefore have the potential to provide the high-brightness, high-current beams required for CW-XFELs. After the demonstration of the first SRF gun in Dresden-Rossendorf, several SRF gun programs based on different approaches have achieved promising progress and even succeeded in routine operation. SRF guns are expected to play an important role in XFEL facilities in the near future. In this paper, we give an overview of design concepts, important parameters and development status of the worldwide SRF gun projects.